2017
DOI: 10.1093/mnras/stx964
|View full text |Cite
|
Sign up to set email alerts
|

Dusty spirals versus gas kinematics in the inner kiloparsec of four low-luminosity active galactic nuclei

Abstract: We used the Gemini Multi-Object Spectrograph (GMOS) Integral Field Unit (IFU) to map the gas distribution, excitation and kinematics within the inner kiloparsec of four nearby low-luminosity active galaxies: NGC3982, NGC4501, NGC2787 and NGC4450. The observations cover the spectral range 5600-7000 Å at a velocity resolution of 120 km s −1 and spatial resolution ranging from 50 to 70 pc at the galaxies. Extended emission in Hα, [N ii]λλ6548,6583, [S ii] λλ6716,6730 over most of the field-of-view is observed for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 87 publications
2
31
1
Order By: Relevance
“…NGC 4450. Brum et al (2017) found a clear rotating disc pattern with the line of nodes oriented along the North-South direction with some deviations. The flat and low amplitude rotation curve presented in Fig.…”
Section: Appendix B: Comments Spectra and Images Of Individual Sourcesmentioning
confidence: 95%
See 1 more Smart Citation
“…NGC 4450. Brum et al (2017) found a clear rotating disc pattern with the line of nodes oriented along the North-South direction with some deviations. The flat and low amplitude rotation curve presented in Fig.…”
Section: Appendix B: Comments Spectra and Images Of Individual Sourcesmentioning
confidence: 95%
“…For ground-based data, this criterion clearly identifies 6 and 3 cases out of 15 with outflows (40 %) and rotation (20 %), respectively ( There are not systematic studies of outflows in type-1 LINERs via ground-based spectroscopy, but only works of individual cases (e.g. Dopita et al 2015;Brum et al 2017). The detection rate of outflows in ground-based data is lower than what found in studies of sample of nearby (z < 0.2) type-2 luminous AGNs and quasars (e.g.…”
Section: Non-rotational Motionsmentioning
confidence: 99%
“…The equation is based on Bertola et al ( 1991 ) and has already been used in previous works by our group using similar data (e.g. Schnorr-M üller et al 2014 ;Diniz et al 2015 ;Brum et al 2017Brum et al , 2019.…”
Section: Rotation Modelsmentioning
confidence: 99%
“…We use the penalized Pixel-Fitting (pPXF) routine (Cappellari & Emsellem 2004;Cappellar 2017) for fitting the absorption spectra of IRAS11506 and measure the stellar kinematics. To perform the measurements we use as spectral templates, the single stellar populations (SSP) models of Bruzual & Charlot (2003), which have similar spectral resolution of the GMOS data and have been previously used to measure the stellar kinematics of nearby galaxies from GMOS-IFU data (Brum et al 2017). The line-of-sight velocity distribution of the stars is assumed to be Gaussian, as we fit only the two first moments (V and σ ).…”
Section: Stellar Kinematicsmentioning
confidence: 99%